CD4+ T Cells of Myasthenia Gravis Patients Are Characterized by Increased IL-21, IL-4, and IL-17A Productions and Higher Presence of PD-1 and ICOS - Çebi, Merve; Durmus, Hacer; Aysal, Fikret; Özkan, Berker; Gül, Gizem Engin; Çakar, Arman; Hocaoglu, Mehmet; Mercan, Metin; Yentür, Sibel P.; Tütüncü, Melih; Yayla, Vildan; Akan, Onur; et al. (Frontiers in Immunology, 2020)
Myasthenia gravis (MG) is an autoimmune disease mediated by autoantibodies predominantly against the acetylcholine receptor (AChR). Specific T cells subsets are required for long-term antibody responses and cytokines secreted mainly from CD4+ T cells regulate B cell antibody production. The aim of this study was to assess the differences in the cytokines of CD4+ T cells and their characterization in MG subgroups as well as the effect of immunosuppressive (IS) therapy on cytokine activity. Clinically diagnosed MG patients with AChR antibodies (AChR-MG) or without detectable antibodies (SN-MG) were included. AChR-MG patients were grouped as IS positive and negative and compared with age- and sex-matched healthy controls (HC). Peripheral blood mononuclear cells were used for ex vivo intracellular cytokine production and subsets of CD4+ T cells and circulating follicular helper T (cTfh) cells were detected phenotypically by the expression of the chemokine and costimulatory receptors. Thymocytes from patients were isolated from thymectomy samples for comparison. IL-21, IL-4 and IL-17A productions in CD4+ T cells were increased in AChR-MG and SN-MG patients compared to HC. IS treatment enhanced IL-10 and reduced IFN- production in AChR-MG patients compared to IS negative patients. Among the CD4+ T cells, Th17 cells were increased in both disease groups. Treatment induced higher proportions of Th2 cells in AChR-MG patients. Both CXCR5+ and CXCR5- CD4+ T cells expressed higher PD-1 and ICOS in AChR-MG and SN-MG groups irrespective of the treatment. Based on chemokine receptors on CXCR5+PD-1+ in CD4+ T (cTfh) cells, the proportions of Tfh17 cells of AChR-MG patients, especially without treatment, were higher and Tfh1 cells were lower. The relevance of PD-1 and CXCR5 in the pathogenesis of AChR-MG was supported by the increased presence of these molecules on mature CD4 single positive thymocytes from thymic samples. The study provides further evidence for the importance of IL-21, IL-17A and IL-4. Disease related CD4+T cells are identified mainly as PD-1+ or ICOS+ with or without CXCR5, resembling cTfh cells in the circulation and in the thymus. Similarities between AChR-MG and SN-MG are demonstrated and the effects of IS treatment on cytokines are shown.